2011
DOI: 10.1021/ac202074s
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Characterization of Buried Nanolayers by Quantitative X-ray Fluorescence Spectrometry under Conventional and Grazing Incidence Conditions

Abstract: The determination of the thickness and elemental composition is an important part of the characterization of nanolayered structures. For buried nanolayers, X-ray fluorescence spectrometry is a qualified method for the thickness determination whereas conventional electron emission based methods may reach their limits due to rather restricted information depths. The aim of the presented investigation was the comparison of reference-free X-ray fluorescence spectrometry under conventional and grazing incidence con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…X-Ray Fluorescence analysis (XRF) is a highly sensitive technique to obtain elemental composition and mass deposition. In particular, XRF in grazing incidence geometry [59] allows for very low limits of detection.…”
Section: Introductionmentioning
confidence: 99%
“…X-Ray Fluorescence analysis (XRF) is a highly sensitive technique to obtain elemental composition and mass deposition. In particular, XRF in grazing incidence geometry [59] allows for very low limits of detection.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon is more efficiently detected by using SR at 3.8 keV excitation energy compared with the 5.41 keV, whereas in the spectrum obtained from the low Z –high Z TXRF spectrometer, the C Kα is almost merged with the O Kα peak. Previous studies have demonstrated the potential of SR to carry out even quantitative XRF and grazing incidence XRF analysis of light elements contained in buried boron and carbon nanolayers on silicon substrate excited optimally by 510 eV undulator radiation and measured by a calibrated setup with a windowless SDD …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the potential of SR to carry out even quantitative XRF and grazing incidence XRF analysis of light elements contained in buried boron and carbon nanolayers on silicon substrate excited optimally by 510 eV undulator radiation and measured by a calibrated setup with a windowless SDD. [29] Total reflection X-ray fluorescence quantification…”
Section: Results and Discussion Detection Limitsmentioning
confidence: 99%
“…Also, due to the shallow incidence angles, the X-ray absorption is quite pronounced in the depth direction, limiting the volume in which X-ray fluorescence is effectively excited. Depth-sensitive measurements of multilayers and thin films deposited on a surface were performed by means of GIXRF [56][57][58][59][60] or by means of XSW under grazing incidence conditions [55,61]. The thickness and the density of the films as well as the elemental amount or quantity of deposited material were assessed.…”
Section: Gixrf and Gexrfmentioning
confidence: 99%